GSH and GABA decreases in IDH1-mutated low-grade gliomas detected by HERMES spectral editing at 3 T in vivo. (December 2020) - Gong, Tao; Zhang, Xia; Wei, Xinhong; Yuan, Shuhui; Saleh, Muhammad G.; Song, Yulu; Edden, Richard A.; Wang, Guangbin
Abstract: Isocitrate dehydrogenase 1 (IDH1) mutational status is an important prognostic biomarker in gliomas. γ-aminobutyric acid (GABA) and reduced glutathione (GSH) play an important role in energy production, which is related to tumor progression. Hadamard Encoding and Reconstruction of Mega-Edited Spectroscopy (HERMES) is able to detect GABA and GSH in healthy controls. This study aims to examine GABA and GSH alterations in IDH1-mutated low-grade gliomas using HERMES. We prospectively enrolled 14 suspected low-grade gliomas and 6 healthy control patients in this study, all cases underwent a 3 T MRI scan, including T1-weighted imaging and HERMES acquisition with a volume of interest 3 × 3 × 3 cm 3 . HERMES detects a "GABA+" signal that includes contributions from macromolecules and homocarnosine. GABA+ and GSH in tumor foci (group 1), contralateral cerebral regions (group 2) and healthy controls (group 3) were quantified using Gannet. The fitting errors and SNR of HERMES for GABA+ and GSH were analyzed; FWHM of the unsuppressed water signal was also recorded. The Wilcoxon signed-rank test was performed to test for differences between contralateral GABA+ and GSH levels, and differences in GABA+, GSH and fitting errors/SNR between the three groups were analyzed using analysis of variance (ANOVA). Eleven IDH1-mutant low-grade gliomas (5 Female and 6 Male, age 33–69) and 6 healthy subjects (2 Female and 4 Male, age 35–60) were finally enrolled this study. The mean water linewidth across all subjects was 9.67 ± 2.28 Hz. The Wilcoxon signed-rank test revealed that GABA+ and GSH were decreased significantly in glioma foci compared with contralateral regions, whereas no differences were seen between the left and right regions in healthy controls. ANOVA showed that GABA+ and GSH levels in tumor were lower than contralaterally and in healthy controls, while no differences were observed between the contralateral healthy tissue and healthy controls. No differences of fitting errors or SNR were found between tumors, contralateral regions or healthy controls. Our results suggest that HERMES is a reliable tool to simultaneously measure GABA and GSH alterations in low-grade gliomas with IDH1 mutations. Highlights: HERMES is a reliable tool to simultaneously measure GABA and GSH levels in IDH1-mutant low-grade gliomas. GABA and GSH both decreased in IDH1-mutant low-grade glioma foci compared with contralateral regions. No differences of GABA and GSH levels were observed between the contralateral brain tissue and healthy controls.